Ang Kababaihang Maykaya, Ang Pakikibaka Para sa Karapatang Bumoto at ang Pagtaguyod sa Kababaihang Manggagawa - Taguiwalo, Judy M. (Philippine Journal of Social Development; 2007, 2010)
The paper delves into the relationship between upper class Filipino women and women workers during the American colonial period. The relationship encompasses the struggle for women’s suffrage led by upper class Filipino women and their support for workers’ struggles.  In the early part of colonial rule, possibly because of  the shared experience of participation in the revolution against Spain and the resistance to American colonialism, upper class women provided direct support to workers’ organizations and struggles. In the last two decades of American colonial rule and with the sharpening of class differentiation among Filipinos, the support given by upper class women to the workers was in the form of projects based on “elite responsibility” for the poor.